Analisis kualitatif: Peran Pola Asuh Orang Tua dalam Membentuk Karakter Disiplin Anak - Alamsyah; Tia Hafizah; Zaini Rahman; Norhalijah Lira Fitria; Muhammad Redha Anshari (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
The formation of children's character is a fundamental aspect of individual development, in which discipline becomes one of the essential values that must be instilled from an early age. This study aims to analyze the influence of parenting styles on the development of children's discipline, particularly at the elementary school age. The method used is a literature review with a descriptive qualitative approach, collecting data from various relevant journals and scientific articles. The results of the study show that democratic parenting has a significant positive impact on children's learning motivation and discipline. Children raised in a supportive environment where they are involved in decision-making processes tend to be more independent and responsible. Conversely, authoritarian and permissive parenting styles show negative impacts. Children raised with an authoritarian approach often face challenges in social interactions and tend to have low self-confidence, while permissive parenting may result in low levels of independence and social skills. In conclusion, the application of a balanced and democratic parenting style is crucial in supporting the development of children's disciplinary character. Therefore, parents, teachers, and policymakers should design more targeted educational approaches.